1995
DOI: 10.1111/j.1365-2265.1995.tb02620.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood IQ measurements in infants with transient congenital hypothyroidism*

Abstract: Infants born and living in an academic goitre area, who had biochemical signs of thyroid hypo-function at birth, had a lower intelligence quotient at the age of 7-8 years than matched controls living in the same environmental conditions but with normal thyroid function at birth. The present findings strongly suggest that abnormalities in thyroid function at birth, even when transient, can adversely affect long-term intellectual development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 18 publications
2
39
1
5
Order By: Relevance
“…However, this approach allows the early diagnosis of fetal hypothyroidism and the provision of substitutive therapy in utero (25,26). Several recent studies have shown that intrauterine hypothyroidism is associated with decreased IQ values at 3-7 years even if a correct neonatal thyroid hormone replacement therapy is provided (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach allows the early diagnosis of fetal hypothyroidism and the provision of substitutive therapy in utero (25,26). Several recent studies have shown that intrauterine hypothyroidism is associated with decreased IQ values at 3-7 years even if a correct neonatal thyroid hormone replacement therapy is provided (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…To date, observations indicate a beneficial therapeutic effect of early treatment. [19][20][21] Studies on this early treatment in neonates are planned for the area serviced by the screening programme in Krakow. The assessment of the psychophysical status of the group at risk should resolve the issue of the validity of introducing rescreening in neonates with low and very low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Elevated serum thyroid-stimulating hormone (TSH) may be due to congenital hypothyroidism or iodine deficiency. [4] Both conditions can result in mental retardation. [5] The World Health Organization (WHO), United Nations International Children's Emergency Fund (UNICEF), and International Council for Control of Iodine Deficiency Disorders (ICCIDD) have made a proposal for assessing iodine deficiency disorders (IDD).…”
Section: Introductionmentioning
confidence: 99%